Characteristics of Briquettes Produced from Rubber Seed Shell and Palm Kernel Shell Using Tapioca Flour as Binder - Farid Jayadi; Devia Gahana Cindi Alfian; Muhammad Hasbi Pratama; Fajar Perdana Nurullah; Dicky Januarizky Silitonga; Lathifa Putri Afisna (Universitas Muhammadiyah Metro, 2025)
Indonesia faces challenges in managing renewable energy as an alternative to fossil fuels. This study aims to compare commercially available briquettes with experimental briquettes produced from a mixture of rubber seed shells and palm shells using tapioca flour as a binder. The raw material composition variations between rubber seed shells and palm shells used were 80:20, 50:50, and 20:80, with 10% tapioca flour binder, and dried at a temperature of 100Â°C for 3 hours. The purpose of this research is to compare the produced briquettes with those already marketed. Based on the experiments and tests carried out, the results show that the 20:80 variation produced briquettes most comparable to the market samples, with a density of 0.7438 g/cmÂ³, moisture content of 3.43%, calorific value of 6849.46 cal/gram, combustion rate of 0.1117 g/minute, and a drop test value of 4.7672%.